Islam, Adat, and State: Examining the Phenomenon of Child Custody After Divorce in Padang Lawas Regency - Hasibuan, Putra Halomoan; Harahap, Sumper Mulia; Mustafid, Mustafid (Hukum Keluarga Islam IAIN LANGSA, 2024)
This research is motivated by the phenomenon of childcare by fathers after divorce in Padang Lawas County. This phenomenon raises the interest of researchers to further examine child custody by fathers after divorce. The research method used is field research with a qualitative approach. Researchers collected primary data through interviews with traditional leaders and fathers caring for their children after divorce. The data obtained was then analyzed using descriptive analysis techniques, which involved collecting data through interviews and documentation and systematic data processing to describe and interpret existing phenomena. The results show that although customs in Padang Lawas County give custody to the father, it is essential to consider the provisions of the compilation of Islamic law and the broader principles of Islamic law. Child custody should focus on the best interests of the child, ensuring their physical, emotional, and mental development. Both parents have equal rights unless there are compelling reasons to the contrary, and they must work together to maintain the child's stability. Children have the right to adequate education and healthcare, as well as to maintain a good relationship with both parents, even if only one has primary custody.